Literature Study: Visual Support Design as Assistive Technology for Children with Autism Spectrum Disorder - Irvan, Muchamad; Jauhari, Muhammad Nurrohman; Wasesa, Andarmadi Jati Abdhi; Rosmi, Yandika Fefrian (Journal of ICSAR, 2023)
Providing interventions for children with autism requires various methods and learning media. Visual Support has long been implemented to help train communication skills in children with autism. Recently, many applications have developed as assistive technology to help children with autism in the learning environment. This study aims to elaborate on the visual design integrated into application-based assistive technology for children with autism. The method used in this research is a Systematic Literature Review. Based on the data tracing results, several references have been collected that specifically discuss the design of visual Support. From the data analysis, it can be concluded that visual Support is important to be integrated into digital applications to help children with ASD to carry out daily activities in various environmental settings. The development of visual support design must refer to the prerequisite rules to support the suitability of their characteristics and needs.